2013
DOI: 10.1158/1078-0432.ccr-12-2199
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 on Tumor Cells Is Induced in Ascites and Promotes Peritoneal Dissemination of Ovarian Cancer through CTL Dysfunction

Abstract: Purpose: Ovarian cancer often progresses by disseminating to the peritoneal cavity, but how the tumor cells evade host immunity during this process is poorly understood. Programmed cell death 1 ligand 1 (PD-L1) is known to suppress immune system and to be expressed in cancer cells. The purpose of this study is to elucidate the function of PD-L1 in peritoneal dissemination.Experimental Design: Ovarian cancer cases were studied by microarray and immunohistochemistry. PD-L1 expression in mouse ovarian cancer cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
181
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(195 citation statements)
references
References 39 publications
9
181
0
5
Order By: Relevance
“…In support of this notion, prior studies have shown that NY-ESO-1-specific CD8 þ TIL from ovarian cancer patients frequently express PD-1 and are functionally impaired compared with their counterparts in peripheral blood (20). Moreover, ovarian tumor cells have been reported to express high levels of PD-L1 (21,22).…”
Section: Introductionmentioning
confidence: 83%
“…In support of this notion, prior studies have shown that NY-ESO-1-specific CD8 þ TIL from ovarian cancer patients frequently express PD-1 and are functionally impaired compared with their counterparts in peripheral blood (20). Moreover, ovarian tumor cells have been reported to express high levels of PD-L1 (21,22).…”
Section: Introductionmentioning
confidence: 83%
“…Modulation of PD-L1 expression may impact the fate of tumor cells and infiltrating immune cells from the microenvironment in adenocarcinomas. [68][69][70][71] After CD39 blockade or IL-27 depletion, the reduced PD-L1 expression by macrophages might affect the ratio of costimulatory vs. coinhibitory molecules in the context of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, given that different immune cell populations are present in malignant PE/ascites, we also focused on the cytotoxicity of immune cells on cancer cells cultured with malignant exudates. Previous studies have shown that malignant PE/ascites foster immune privilege and facilitate tumor cell survival (39,40). One of these reports shows that tumor cells in the peritoneal cavity express PD-L1 and escape from CD8ϩ cytotoxic lymphocytes (40).…”
Section: Discussionmentioning
confidence: 99%